Grossulariaceae endémicas del Perú - Mendoza, Wilfredo (2006)
The Grossulariaceae are represented in Peru by three genera and nearly 35 species (Brako & Zarucchi, 1993; Weigend & Rodriguez, 2006 ), all shrubs and trees. Here we recognize 11 endemic species in two genera. Ribes is the genus with the largest number of endemic species. Endemic Grossulariaceae species grow mainly in Humid and Dry Puna, and Very Humid Montane Forest regions, between 2500 and 4600 m elevation. Two endemic Grossulariaceae have been registered to date in the Peruvian protected areas system.